Program CERAH: Edukasi Interaktif Reduce, Reuse, Recycle (3R) untuk Meningkatkan Pengetahuan Pengelolaan Sampah pada Siswa SDN 7 Lubai Ulu Desa Sumber Mulya, Kabupaten Muara Enim: The CERAH Program: Interactive 3R (Reduce, Reuse, Recycle) Education to Enhance Waste Management Knowledge among Elementary School Students at SDN 7 Lubai Ulu, Sumber Mulya Village, Muara Enim Regency - Dwi Fitriani; Diva Salsabila Apyudri; Meysah Rista Putri; Lucky Arzia; Prisda Rahmawati; Nur Hasanah; Mutiara Putri Rizanti (Poltekkes Kemenkes Yogyakarta, 2025)
Waste management remains a major environmental health issue in Indonesia, particularly in rural areas where waste management facilities and environmental education are still limited. This condition may increase the risk of environmental pollution and unhealthy behaviors among school-aged children. This community service program aimed to improve elementary school students’ knowledge regarding the 3R concept (Reduce, Reuse, Recycle) through the CERAH program (Smart Counseling on 3R for School Children). The activity was conducted on June 3, 2025, at SD Negeri 7 Lubai Ulu, Muara Enim Regency, South Sumatra, involving 29 fifth-grade students aged 10–12 years. The intervention employed a promotive educational approach using participatory methods, including interactive lectures, PowerPoint presentations, educational posters, 3R-themed songs, ice-breaking activities, and question-and-answer sessions. Evaluation was carried out using pre-test and post-test instruments consisting of five multiple-choice questions to assess students’ knowledge improvement. The results demonstrated a significant increase in students’ understanding after the intervention, as indicated by the improvement in the average score from 2.41 to 4.83, with the Paired Samples T-Test showing a statistically significant difference (p=0.000). In addition, almost all participants were able to answer all post-test questions correctly. This program indicates that environmental education based on visual media and interactive approaches is effective in improving waste management literacy among elementary school students and has the potential to foster environmentally responsible behavior from an early age.